Dynamic Analysis of Photosynthate Translocation Into Strawberry Fruits Using Non-invasive 11C-Labeling Supported With Conventional Destructive Measurements Using 13C-Labeling - Hidaka, Kota; Miyoshi, Yuta; Ishii, Satomi; Suzui, Nobuo; Yin, Yong-Gen; Kurita, Keisuke; Nagao, Koyo; Araki, Takuya; Yasutake, Daisuke; Kitano, Masaharu; Kawachi, Naoki (Frontiers in Plant Science, 2019)
In protected strawberry (Fragaria × ananassa Duch.) cultivation, environmental control based on the process of photosynthate translocation is essential for optimizing fruit quality and yield, because the process of photosynthate translocation directly affects dry matter partitioning. We visualized photosynthate translocation to strawberry fruits non-invasively with 11CO2 and a positron-emitting tracer imaging system (PETIS). We used PETIS to evaluate real-time dynamics of 11C-labeled photosynthate translocation from a 11CO2-fed leaf, which was immediately below the inflorescence, to individual fruits on an inflorescence in intact plant. Serial photosynthate translocation images and animations obtained by PETIS verified that the 11C-photosynthates from the source leaf reached the sink fruit within 1 h but did not accumulate homogeneously within a fruit. The quantity of photosynthate translocation as represented by 11C radioactivity varied among individual fruits and their positions on the inflorescence. Photosynthate translocation rates to secondary fruit were faster than those to primary or tertiary fruits, even though the translocation pathway from leaf to fruit was the longest for the secondary fruit. Moreover, the secondary fruit was 25% smaller than the primary fruit. Sink activity (11C radioactivity / dry weight [DW]) of the secondary fruit was higher than those of the primary and tertiary fruits. These relative differences in sink activity levels among the three fruit positions were also confirmed by 13C tracer measurement. Photosynthate translocation rates in the pedicels might be dependent on the sink strength of the adjoining fruits. The present study established 11C-photosynthate arrival times to the sink fruits and demonstrated that the translocated material does not uniformly accumulate within a fruit. The actual quantities of translocated photosynthates from a specific leaf differed among individual fruits on the same inflorescence. To the best of our knowledge, this is the first reported observation of real-time translocation to individual fruits in an intact strawberry plant using 11C-radioactive- and 13C-stable-isotope analyses.